(untitled) (Environment & Health, 2015)
Objective: to study the characteristics of the basin pollution by mobile sources. Materials and methods: industrial air emissions of the industrial city from stationary and mobile sources; analysis and synthesis of modern scientific publications on air pollution of industrial cities. Results. In the modern period in the industrial cities of the volume of industrial emissions from stationary and mobile sources is inherent in opposite changes. Against the background of reduction of emissions from stationary sources, emissions from mobile sources has increased significantly. As a consequence, the share of mobile sources increased to a third of total emissions. The progressive increase in road transport as a man-made air pollution changes the range and volume of toxicants. From mobile sources air swimming pool industrial city most polluted dioxide and carbon monoxide, non-methane volatile organic compounds, nitrogen oxide and dioxide.